Quando A= -1 e B= -0,1 , Qual é o valor numérico da expressão: A³-B³+3AB²-3A²B?
Soluções para a tarefa
Respondido por
5
a³ -b³ + 3ab² - 3a²b = para a = -1 e b = -0,1 substituindo
(-1)³ -(-0,1)³ + 3.(-1).(-0,1)² -3.(-1)².(-0,1) =
-1 - (-0,001 + (-3).(+0,01) -3.(+1).(-1)) =
-1 - (-0,001 - 0,003 -3 .(-1) =
-1 - (-0,001 - 0,003 +3) =
-1 +0,001 +0,003 -3 =
\ /
-1 + 0,004 -3 =
-4 + 0,004 = 3,996
(-1)³ -(-0,1)³ + 3.(-1).(-0,1)² -3.(-1)².(-0,1) =
-1 - (-0,001 + (-3).(+0,01) -3.(+1).(-1)) =
-1 - (-0,001 - 0,003 -3 .(-1) =
-1 - (-0,001 - 0,003 +3) =
-1 +0,001 +0,003 -3 =
\ /
-1 + 0,004 -3 =
-4 + 0,004 = 3,996
Perguntas interessantes